Kinetics of Oxidation of Cycloheptanol by Os(VIII) Continuously regenerated by Hexacyanoferrate(III) Ions - K. Sati, Mukul; Singh, Pratibha; Tewary, Geeta; Mehta, S.P.S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of cycloheptanol by Os(VIII) continuously regenerated by hexecyanofarrate (III) ions was studied in the 0.01 M–0.1 M [OH– ] range. The rate law derived on the basis of the mechanism suggested was :